CONSTRUCTION OF COOPERATIVE FINANCIAL STATEMENTS BASED ON SAK ETAP - Ashfahany, Muhammad Numan; Nawirah, Nawirah (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
The aim of this research is to analyze and construct cooperative financial statements. This type of research is qualitative research using a descriptive approach. The object of the research is the Mandiri Multipurpose Cooperative whose address is Pasuruan Regency. Analysis techniques are used with the aim of finding out how the financial statementss of the Mandiri Multipurpose Cooperative are prepared using the accounting cycle treatment, then the financial statements will be reviewed based on SAK ETAP. The next stage is to construct financial statements in accordance with SAK ETAP which has been approved by the Indonesian Accountants Association. This research provides results that the accounting cycle treatment only carries out the recording and reporting stages. The Mandiri Multipurpose Cooperative has prepared 3 components of financial statements, namely a balance sheet, a report on the calculation of remaining business results, and notes to the financial statements. However, there are several financial statements that have not been prepared when referring to SAK ETAP, namely reports on changes in equity and cash flow reports.